Authentic Assessment of Attitudes in Islamic Religious Education Subjects in the Formation of Students' Religious Character at SMAN 7 Sijunjung - Amri, Ulil (Ruhama : Islamic Education Journal, 2024)
This article discusses the Authentic Assessment of Attitudes in Islamic Religious Education Subjects in the Formation of Students' Religious Character at SMAN 7 Sijunjung. This research is field research which tries to maximally reveal facts from the field qualitatively through scientific methods with clear data collection and data analysis techniques. descriptive qualitative research method. The subjects in this research were the principal, head of curriculum and PAI teachers at SMAN 7 Sijunjung. The data collection instruments and procedures used were interviews, observation and documentation. Research results: 1) The process of authentic assessment of attitude aspects in Islamic Religious Education subjects and their impact on the formation of students' religious character is taken by observing teachers, peers, teachers' daily journals, peer assessments, then reported to the curriculum to be made into report cards. every semester, from processing grades for PAI teachers to reporting authentic grades with medium (grades that appear frequently) and not average, reported in letter form (A = very good, B = good, C = fair, D = poor), 2) The results of the authentic assessment of the attitude aspect in the subject of Islamic Religious Education and its impact on the formation of students' religious character are very good and positive, where students have started to participate in midday congregational prayers at school, students always pray fervently, students also read the Asmaul Husna. looks unified, more polite, pays more attention to congregational prayer times, 3) Factors that support PAI teachers in carrying out authentic assessment of attitudes in Islamic religious education subjects in forming the religious character of students at SMA 7 Sijunjung are 1) facilities and factors adequate infrastructure, 2) time adapted to needs, and 3) a congregational prayer program. Factors that hinder PAI teachers in carrying out authentic assessment of attitudes in Islamic religious education subjects in forming the religious character of students at SMA 7 Sijunjung, are not carried out specifically, such as in authentic cognitive assessment, problems with assessment time, sometimes PAI teachers have to cover the material that must be taught. delivered to students in order to achieve curriculum targetskeyword :Authentic Assessment , Attitudes, Islamic Religious Education,  Religious Character